Numerical Simulation of Flood Intrusion Process under Malfunction of Flood Retaining Facilities in Complex Subway Stations - Zhiyu Lin; Shengbin Hu; Tianzhong Zhou; Youxin Zhong; Ye Zhu; Lei Shi; Hang Lin (Buildings, 2022)
In recent years, heavy rain and waterlogging accidents in subway stations have occurred many times around the world. With the comprehensive development trend of underground space, the accidents caused by flood flow intruding complex subway stations and other underground complexes in extreme precipitation disasters will be lead to more serious casualties and property damage. Therefore, it is necessary to conduct numerical simulation of flood intrusion process under malfunction of flood retaining facilities in complex subway stations. In order to prevent floods from intruding subway stations and explore coping strategies, in this study, the simulation method was used to study the entire process of flood intrusion into complex subway stations when the flood retaining facilities fail in extreme rain and flood disasters that occur once-in-a-century. The three-dimensional numerical simulation model was constructed by taking a subway interchange station with a property development floor in Nanning as a prototype. Based on the Volume of Fluid (VOF) model method, the inundated area in the subway station during the process of flood intrusion from the beginning to the basic stability was simulated, and it was found that the property development floor has serious large-scale water accumulation under extreme rainfall conditions. Through the dynamic monitoring of the flood water level depth at important positions such as the entrances of the evacuation passages, and the analysis of the influence of the design structure and location distribution of different passages on the personnel evacuation plan, it was found that the deep water accumulation at the entrances of the narrow, long, and multi-run emergency safety passages are not conducive to the evacuation of personnel. Finally, the flow of flood water into the subway tunnel through the subway station was calculated. The research results provide certain reference and guidance for the safety design of subway stations under extreme rainfall climatic conditions.